International treaty as a source of financial law in Ukraine - Yuriy Onischyk; Olena Maidannyk; Yaroslav Zhuravel; Pavlo Selezen (Juridical Tribune, 2020)
Double taxation agreement is one of the most widespread type of international treaty regulating financial relations. The efficiency of its application as a source of financial law depends on the features of the legal basis for implementation of its provisions into domestic legal orders of contracting states. Based on the practice of Ukraine, there is an attempt to describe key challenges in application of provisions of international treaties in the context of the requirements of the Tax Code of Ukraine based on the application of comparative method: 1) the legal status of double taxation treaties of Ukraine that are still in effect based on the fact of legal succession of Ukraine; 2) the legal status of protocols to international treaties concluded between competent authorities of contracting states; 3) the legal status of mutual agreements concluded on the basis of the provisions of double taxation treaties.